Implementasi Radio Frequency Identification (RFID) dengan PIECES di Perpustakaan Penerbitan Percetakan Universitas Negeri Padang - Halim, Ari Gunawan; Desriyeni, Desriyeni (Scinary, 2025)
This research aims to describe how the implementation of Radio Frequency Identification (RFID) as a collection security system in the Printing Publishing Library of Padang State University with PIECES analysis. This research is descriptive qualitative research. Determination of informants in this study was carried out by purposive sampling method. Data collection was done by observation, interview, and literature study. Data validation was done through source triangulation which was then analysed with qualitative data analysis techniques by Miles and Huberman. The results showed that: (1) performance RFID in the library includes easy and fast access to information and identification of library materials; (2) information RFID produces accurate and relevant information; (3) econonmy RFID in the library only has procurement costs at the beginning of installation, but as the number of books that must be installed RFID decreases, the budget began not to be submitted. The resources are librarians and also components that are integrated with RFID; (4) control RFID in the library has not been accompanied by routine maintenance; (5) efficiency RFID is considered quite good starting from the efficiency of time, energy, and the way RFID works itself; and (6) the service provided using RFID is fast and is a small step for the library in improving service quality.